Media Pembelajaran Sistem Kendali Lampu Dengan Handdetection Berbasis Aplikasi Pycharm Pada Mata Kuliah Sistem Kendali - Kadek Oky Yunantara; I Gede Made Surya Bumi Pracasitaram; Wayan Mahardika Prasetya Wiratama (Jurnal Pendidikan Teknik Elektro Undiksha, 2022)
This study aimed to create a Light Control System Learning Media with Hand detection based on the Pycharm Application that can assist the learning process, determine the feasibility of learning media, and find out the excellent response from students in the control system course in the Electrical Engineering Education Study Program, Undiksha. This research was classified as R&D (Research and Development) research and used a statistical analysis to process percentages of content experts, media experts, and field trials. This study used a questionnaire to collect data from content experts, media experts, and students. The research results obtained: the results of the media expert test got a percentage of 98.66% with very decent qualifications, and the content expert validation test got a percentage of 96.36% with very proper qualifications. The score range for the six small group test respondents is all listed in the very high classification, and the score range for the 20 large group test respondents is all listed in the very high category. The Light Control System Learning Media with Pycharm application-based hand detection in the Undiksha Electrical Engineering Education S1 Study Program is suitable for use in the learning process.